CRISPR/Cas Genome Editing—Can It Become a Game Changer in Future Fisheries Sector? - Roy, Suvra; Kumar, Vikash; Behera, Bijay Kumar; Parhi, Janmejay; Mohapatra, Sipra; Chakraborty, Tapas; Das, Basanta Kumar (Frontiers in Marine Science, 2022)
Fisheries and aquaculture are the fastest-growing food-producing sector and rapidly becoming an important element for the global food security since they are the primary source of seafood and high animal protein in the human diet. Genome editing offers new possibilities such as the clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR-associated protein (Cas9) technology, which has the potential to accelerate the sustainable genetic improvement in fisheries and aquaculture. The CRISPR/Cas9 system has four key components, namely, target DNA, Cas9, the protospacer adjacent motif sequence, and the guide RNA or single-guide RNA. CRISPR/Cas is cheaper, easier, and more precise than the other genome editing technologies and can be used as a new breeding technology in fisheries and aquaculture to solve the far-reaching challenges. The attributes like high fecundity, external fertilization, short generation interval, the established method of breeding, and the larval rearing of most aquaculture species have advantages for CRISPR/Cas9 genome editing applications. CRISPR/Cas9 has recently been applied to the traits valued in some aquaculture species (almost >20 species), targeting the main traits of traditional genetic improvement initiatives like growth, disease resistance, reproduction, sterility, and pigmentation. Genome editing can fast forward the breeding process with precision where changes occur in the targeted genes. The probability of desired changes occurring and passing the trait in the next generation is high, so it takes 1-3 generations to establish a breed. Moreover, CRISPR/Cas genome editing rapidly introduces favorable changes by disrupting genes with targeted minor changes, in contrast to transgenesis, which introduces foreign genes into the host genome and thereby alleviates major public concerns on safety. Although the CRISPR/Cas technology has a tremendous potential, there are several technical challenges and regulatory and public issues concerning the applications in fisheries and the aquaculture breeding sector. Nonetheless, the exciting point in the CRISPR/Cas9 genome editing is that two CRISPR-edited fish, namely, red sea bream and tiger puffer developed by the Kyoto-based startup got approval and are now on the market for sale, and another fish, FLT-01 Nile tilapia developed by the AquaBounty, is not classified under genetically modified organism regulatory. However, there is still a way to go before it revolutionizes and becomes viable in commercial aquaculture as the new breeding technology for aquaculture-important traits and species.